Pendampingan Manajemen Dan Tata Kelola Masjid Bagi Pengurus Yayasan Dan Takmir Masjid Di Kecamatan Batang Batang Sumenep - Musayyidi, Musayyidi; Hafid, Hafid; Hairiyah, Sitti (PELITA NUSA TENGGARA, 2025)
Mosques have a strategic role not only as places of worship but also as centers for social activities, education, and community empowerment. However, mosque management at the local level often still faces various challenges, such as limited management capacity, a lack of structured governance systems, and minimal understanding among administrators regarding managerial functions in managing mosque organizations.The mentoring program on mosque management and governance for foundation administrators and mosque caretakers (takmir) in Batang-Batang District, Sumenep Regency, aims to enhance the capacity of administrators to manage mosques in a professional, transparent, and accountable manner. The methods used in this program include training sessions, participatory discussions, and assistance in developing mosque management and administrative systems. The results of the program indicate an improvement in the administrators’ understanding of program planning, financial management, organizational administration, and strengthening the role of the mosque as a center for community empowerment. Through this mentoring initiative, it is expected that mosque management in Batang-Batang District will operate more effectively and sustainably, while also providing broader contributions to the surrounding community.